Study of Influence of Different Models of E-Learning Content Product Design on Students' Learning Motivation and Effectiveness - Shieh, Meng-Dar; Hsieh, Hsin-Yin (Frontiers in Psychology, 2021)
As teachers provide one-way teaching demonstration or reference materials in class, students lack of the opportunities for direct operation. The provision of interactive e-materials could reduce the need for instructors to prepare complicated teaching aids and could deal with issues of climate and location. Learners could learn any time, anywhere, and learning could be reinforced by repeating the instruction with no need to disrupt timetables. The participants in the experimental teaching study were 275 product design students who engaged in e-learning for 15 weeks (3 h per week for a total of 45 h). The research results are summarized as follows: (1) Interactive teaching materials can enhance students’ active learning styles so that, in the product design area, this method could reduce learning differences in students. (2) E-materials deliver knowledge using simple and specific images, animation, audio, and video, making learning interesting and relaxed for the product design students. E-learning is easy and practical and reduces learners’ cognitive load. (3) Students’ cognitive development and prior knowledge should be considered in the development of e-materials. Simple images, animations, text, and language could improve the attention and learning motivation of product design students and allow students to learn based on prior knowledge. A suggestion, based on the findings, is the application of various communication teaching models using e-materials to course work for the product design students, enabling discussion, analysis, concept formation, and problem-solving.